High sucrose consumption induces memory impairment in rats associated with electrophysiological modifications but not with metabolic changes in the hippocampus. (19th February 2016) - Lemos, C.; Rial, D.; Gonçalves, F.Q.; Pires, J.; Silva, H.B.; Matheus, F.C.; da Silva, A.C.; Marques, J.M.; Rodrigues, R.J.; Jarak, I.; Prediger, R.D.; Reis, F.; et al.
Highlights: High sucrose consumption leads to cognitive and emotional impairments in rats. High sucrose consumption does not trigger metabolic alterations in the hippocampus. High sucrose consumption impairs synaptic plasticity in the temporoammonic pathway. High sucrose consumption up-regulates adenosine A1 receptors in the hippocampus. Abstract: High sugar consumption is a risk factor for metabolic disturbances leading to memory impairment. Thus, rats subject to high sucrose intake (HSu) develop a metabolic syndrome and display memory deficits. We now investigated if these HSu-induced memory deficits were associated with metabolic and electrophysiological alterations in the hippocampus. Male Wistar rats were submitted for 9 weeks to a sucrose-rich diet (35% sucrose solution) and subsequently to a battery of behavioral tests; after sacrifice, their hippocampi were collected for ex vivo high-resolution magic angle spinning (HRMAS) metabolic characterization and electrophysiological extracellular recordings in slices. HSu rats displayed a decreased memory performance (object displacement and novel object recognition tasks) and helpless behavior (forced swimming test), without altered locomotion (open field). HRMAS analysis indicated a similar hippocampal metabolic profile of HSu and control rats. HSu rats also displayed no change of synaptic transmission and plasticity (long-term potentiation) in hippocampal Schaffer fibers-CA1 pyramid synapses, but had decreased amplitude of long-term depression in the temporoammonic (TA) pathway. Furthermore, HSu rats had an increased density of inhibitory adenosine A1 receptors (A1 R), that translated into a greater potency of A1 R in Schaffer fiber synapses, but not in the TA pathway, whereas the endogenous activation of A1 R in HSu rats was preserved in the TA pathway but abolished in Schaffer fiber synapses. These results suggest that HSu triggers a hippocampal-dependent memory impairment that is not associated with altered hippocampal metabolism but is probably related to modified synaptic plasticity in hippocampal TA synapses